Heart rate variability during asymptomatic periods in children with recurrent neurocardiogenic syncope - Akçaboy, Meltem; Atalay, Semra; Uçar, Tayfun; Tutar, Ercan (The Turkish Journal of Pediatrics, 2011)
Neurocardiogenic syncope (NS) is a common clinical problem during childhood. In order to characterize the autonomic profile in syncopal children, we evaluated heart rate variability (HRV) of 27 patients, ages 8-17 years, in an asymptomatic period. HRV was calculated over a 24-hour (h) period for the time-domain indices and frequency-domain indices. The obtained results were compared to values in 27 healthy children, ages 10-17 years. Patients with syncope did not have significantly different HRV values in comparison to healthy children. After behavior modification and education, HRV assessment was repeated six months later in the symptomatic group under follow-up, and we found no significantly different values. We conclude that there was no significant difference in baseline autonomic values between children with NS and the healthy control group. After behavior modification and education, none of the patients with NS under follow-up experienced syncope or presyncope during the follow-up period. The major complaint had disappeared but did not reflect the HRV values. There was no significant difference in baseline HRV values of the patients in follow-up. We conclude that patients are predisposed to faint by a triggering autonomic stress, without having constant autonomic instability.